Assessing the Influence of Geopolitical Risks and Indian Uncertainty Index on Energy Sector with VECM - Meher, Bharat Kumar; Anand, Abhishek; Frank, Daniel; Das, Sanjay Kumar; Singh, Manohar (International Journal of Energy Economics and Policy, 2025)
The energy industry is susceptible to geopolitical challenges, like armed conflicts, international disputes, and diplomatic tensions. These factors can result in disruptions to energy supplies, instability in energy prices, and shifts in energy-related policies and strategies. This study explores the impact of Geopolitical Risk (GPR) and India News-Based Policy Uncertainty Index on India’s Energy Sector. To achieve this, several GPR indices and the India News-Based Uncertainty Index is employed as explanatory variables. Response variables to develop a Vector Error Correction Model (VECM) comprised monthly values of the energy index, prices of energy commodities, and stock prices of the top three companies. The analysis encompassed data from February 2011 to August 2023, totaling 151 data points. Contrary to the established theory that suggests that GPR significantly affects crude oil prices, this study finds no supportive evidence, indicating that neither the GPR indices nor the India News-Based Policy Uncertainty Index are statistically significant within the VECM framework. This nuanced analysis highlights the complex interrelationship between geopolitical risks, uncertainty, and different segments of India’s energy market.